Peran Modal Sosial dalam Pemulihan dan Penguatan Perempuan Korban Konflik di Aceh - Liata, Nofal; Fatimahsyam, Fatimahsyam; Furqan, Furqan; Furqan, M. (Department of Anthropology, 2025)
Armed conflict in Aceh has left long-term social consequences for women, particularly those who experienced sexual violence and the loss of family members. These impacts are not limited to psychological trauma but also involve structural vulnerability that restricts women’s access to social and economic resources in the post-conflict period. This study aims to examine the role of social capital in the recovery and empowerment of women survivors of conflict in Gampong Cot Tunong, Pidie Regency, by exploring the interconnections between traumatic experiences, community support, and the role of local institutions. This research employs a qualitative approach using a case study design. Data were collected through in-depth interviews and participant observation involving women survivors of conflict, village officials, and facilitators from a local institution, Pengembangan Aktivitas Sosial Ekonomi Masyarakat (PASKA). The data were analyzed thematically to identify patterns of structural vulnerability, experiences of trauma and social silence, and forms of social capital that have developed within the community of women survivors. The findings indicate that women survivors of conflict face multiple layers of vulnerability arising from sexual violence, the loss of family members, and limited access to public services. Nevertheless, social capital formed through trust-based relationships, solidarity among survivors, support from the village community, and facilitation by local institutions plays a crucial role in trauma recovery and the strengthening of women’s socio-economic lives. Social capital functions not only as a survival mechanism but also as a space for psychosocial recovery and collective empowerment. This study highlights that the recovery of women survivors of conflict should be understood as a social process rooted in community dynamics and the strength of local social capital. Abstrak: Penelitian Konflik bersenjata di Aceh meninggalkan dampak sosial yang berkelanjutan terhadap kehidupan perempuan, khususnya mereka yang mengalami kekerasan seksual dan kehilangan anggota keluarga. Dampak tersebut tidak hanya berupa trauma psikologis, tetapi juga kerentanan struktural yang membatasi akses perempuan terhadap sumber daya sosial dan ekonomi pascakonflik. Penelitian ini bertujuan untuk menganalisis peran modal sosial dalam proses pemulihan dan penguatan perempuan korban konflik di Gampong Cot Tunong, Kabupaten Pidie, dengan menyoroti keterkaitan antara pengalaman trauma, dukungan komunitas, dan peran lembaga lokal. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara mendalam dan observasi partisipatif terhadap perempuan korban konflik, aparat gampong, serta pendamping dari lembaga lokal Pengembangan Aktivitas Sosial Ekonomi Masyarakat (PASKA). Analisis data dilakukan secara tematik untuk mengidentifikasi kerentanan struktural, pengalaman trauma dan keheningan sosial, serta bentuk-bentuk modal sosial yang berkembang dalam komunitas perempuan korban konflik. Hasil penelitian menunjukkan bahwa perempuan korban konflik menghadapi kerentanan berlapis yang bersumber dari kekerasan seksual, kehilangan anggota keluarga, dan keterbatasan akses terhadap layanan publik. Namun demikian, modal sosial yang tumbuh melalui relasi saling percaya, solidaritas sesama korban, dukungan masyarakat gampong, serta pendampingan lembaga lokal berperan penting dalam pemulihan trauma dan penguatan kehidupan sosial-ekonomi perempuan korban konflik. Modal sosial tidak hanya berfungsi sebagai mekanisme bertahan hidup, tetapi juga sebagai ruang pemulihan psikososial dan pembangunan kemandirian secara kolektif. Penelitian ini menegaskan bahwa pemulihan perempuan korban konflik perlu dipahami sebagai proses sosial yang berakar pada dinamika komunitas dan kekuatan modal sosial lokal.